Solubilization of beclomethasone dipropionate in sterically stabilized phospholipid nanomicelles (SSMs): physicochemical and in vitro evaluations - Peh KK; Darwis Y; Abdulameer SA; Sahib MN; Tan YT (Dove Medical Press, 2012)
Mohanad Naji Sahib, Shaymaa Abdalwahed Abdulameer, Yusrida Darwis, Kok Khiang Peh, Yvonne Tze Fung TanSchool of Pharmaceutical Sciences, Universiti Sains Malaysia, Penang, MalaysiaBackground: The local treatment of lung disorders such as asthma and chronic obstructive pulmonary disease via pulmonary drug delivery offers many advantages over oral or intravenous routes of administration. This is because direct deposition of a drug at the diseased site increases local drug concentrations, which improves the pulmonary receptor occupancy and reduces the overall dose required, therefore reducing the side effects that result from high drug doses. From a clinical point of view, although jet nebulizers have been used for aerosol delivery of water-soluble compounds and micronized suspensions, their use with hydrophobic drugs has been inadequate.Aim: To evaluate the feasibility of sterically stabilized phospholipid nanomicelles (SSMs) loaded with beclomethasone dipropionate (BDP) as a carrier for pulmonary delivery.Methods: 1,2-Distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxy-poly(ethylene glycol 5000) polymeric micelles containing BDP (BDP-SSMs) were prepared by the coprecipitation and reconstitution method, and the physicochemical and in vitro characteristics of BDP-SSMs were investigated.Results: BDP-SSMs were successfully prepared with a content uniformity and reproducibility suitable for pulmonary administration. The maximum solubility of BDP in SSMs was approximately 1300 times its actual solubility. The particle size and zeta potential of BDP-SSMs were 19.89 ± 0.67 nm and -28.03 ± 2.05 mV, respectively. The SSMs system slowed down the release of BDP and all of the aerodynamic values of the aerosolized rehydrated BDP-SSMs were not only acceptable but indicated a significant level of deposition in the lungs.Conclusion: The SSM system might be an effective way of improving the therapeutic index of nebulized, poorly soluble corticosteroids.Keywords: beclomethasone, PEGylated polymer, aerodynamic, in vitro dissolution